2008
DOI: 10.1111/j.1439-0523.2008.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Barley adaptation and improvement in the Mediterranean basin

Abstract: To study barley adaptation and improvement in the Mediterranean basin, a collection of 188 entries comprising landraces and old genotypes and current modern varieties from the Mediterranean basin and elsewhere was tested on moisture-contrasted environments in seven Mediterranean countries, during 2004 and 2005 harvest seasons. The experimental design consisted of an unreplicated trial for all entries, augmented by four repeated checks to which a partial replicate containing a quarter of the entries was added. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
2
23
0
2
Order By: Relevance
“…The general pattern of genotype adaptation, determined by the relative performance of the different genotypes in individual trials, coincided with many reports such as those by Ceccarelli (1996a) and Pswarayi et al (2008). Landraces were particularly adapted to low yield potential environments while cultivars adapted best to high yielding trials (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The general pattern of genotype adaptation, determined by the relative performance of the different genotypes in individual trials, coincided with many reports such as those by Ceccarelli (1996a) and Pswarayi et al (2008). Landraces were particularly adapted to low yield potential environments while cultivars adapted best to high yielding trials (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Studies of barley adaptation to drought conditions confirmed the loss of drought tolerance due to breeding and selection, as reported by Forster et al (2000). Many results from adaptation studies have shown that landraces were better adapted to stress environments, while modern genotypes were better adapted to stress-free, high yielding environments (Ceccarelli 1996a;Pswarayi et al 2008). Landraces could be used as a source of genes for adaptation to low yielding environments characterised by drought stresses, limited moisture availability, low fertility, and other related factors.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This supports this idea that positive genetic gains in breeding programs more limited in environments with more stresses. This agrees with the findings of Ceccarelli (1996), Munoz et al (1998Munoz et al ( ), donmez et al (2001, Voltas et al (2002) and Pswarayi et al (2008). however, achieving genetic gains in yield in stressful environments has been recognized to be a difficult challenge for plant breeders, while progress in yield gains has been much higher in non-stressed environments (Richards et al, 2002;Villegas et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Previously used-and-relinquished fields are available for reuse in the future. Farming returns are calculated per-plot by the average of three regression formulas, each calculated from empirical data about the effect of soil depth, soil fertility, and rainfall on wheat and barley yields in Mediterranean climate regimes, and calibrated to typical yields of ancient wheat and barley varieties [39][40][41][42][43][44][45][46][47][48].…”
Section: Human Land-use Modelmentioning
confidence: 99%